Analysis of human mechanics structure in national Tai Chi movement. (3rd April 2020) - Wang, Feng
Tai Chi is an excellent traditional culture of the Chinese nation and a treasure of traditional national sports. It has been developing since thousands of years and is increasingly loved by more and more people at home and abroad. Because of the development of the times and the influence of the change of value orientation of Tai Chi and other factors, people's understanding of many problems of Tai Chi such as theory and method has been biased, which makes the idea of action and skill weakening and action not uniform in the process of inheritance and development of Tai Chi routines. Even the prescribed routines may be practiced and understood differently. To inherit, develop, and disseminate Tai Chi better, these traditional valuable experiences should be made scientific and standardized. With the help of the research method of sports human mechanics and advanced experimental instruments (Xsens MVN system), this article studies and analyzes the human mechanics of the main movements of traditional Yang and Wu Tai Chi, which are the most popular. This provides a scientific experimental basis for the technical research of Tai Chi. The results show that there is no significant difference between Wu-style Tai Chi and Yang-style Tai Chi practitioners in the percentage of body weight in front leg, knee joint, and sole pressure, but there is significant difference in the percentage of body weight in back leg. As a result, the foot pressure gap between Yang-style Tai Chi and Wu-style Tai Chi is smaller, while the foot pressure gap between Wu-style Tai Chi and Wu-style Tai Chi is larger. There were no significant differences in trunk force, front hip force, back hip force, front knee force, and back knee force ( p > 0.05).